Comparative bone identification : human subadult and nonhuman - a field guide - France, Diane L. (Milton Park, Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
"Building on the success, and maintaining the format, of Comparative Bone Identification: Human Subadult and Non-Human (ISBN: 9780367777883), Comparative Bone Identification: Human Subadult and Non-Human - A Field Guide presents new images of human bones representing many states of maturation from neonate to 20 years old in comparison to a variety of animal species' bones. Highly illustrated, the book takes a visual approach and provides full annotations pointing out salient features of the most commonly discovered bones. This includes smaller bones of fetuses and subadult humans in comparison to bones of birds, reptiles, marine mammals, fish, and a frog that human bones may most be confused with. Full-color photos provide clear examples for use by law enforcement, medicolegal death investigators, forensic anthropologists, students, and readers who wish to distinguish between human bones and those of a variety of animal species. The book is not intended to be an exhaustive guide to human and nonhuman skeletons. It offers myriad photos and illustrations to help aid in identification and avoid some of the more commonly confused animal bones for human. The book begins with an introduction section on general osteology and explains the major anatomical differences between humans and other animals. The second section compares human and nonhuman bones, categorized by type of bone, and includes most of the major bones in humans and nonhumans. The third section presents of radiographs illustrated documented age in humans. Conveniently designed for field use, Comparative Bone Identification: Human Subadult to Nonhuman - A Field Guide offers users a practical comparative guide that presents the differences among species for nearly all bones in the body. The book serves as a valuable resource of easy-to-access information to investigators and forensic anthropologists for use in the laboratory or in the field"--
OCLC-licensed vendor bibliographic record.
Keywords: Bones -- Identification; Anatomy, Comparative; Forensic anthropology; SOCIAL SCIENCE / Anthropology / Physical; MEDICAL / Forensic Medicine; SCIENCE / Life Sciences / Zoology / General